PENINGKATKAN HASIL BELAJAR GEOGRAFI MATERI DASAR-DASAR PEMETAAN DENGAN MODEL BELAJAR THINK-PAIR-SHARE (TPs) PADA PESERTA DIDIK KELAS X SMA NEGERI 1 BULU KABUPATEN SUKOHARJO - Tumini, Tumini (Jurnal Pendidikan Ilmu Sosial, 2017)
This classroom action research is conducted to reveal the application of cooperative learning with Â Think-Pair-Share model to learners' learning outcomes on geography subjects of mapping basics. The type of this research is action research which carried out 2 cycles. Each cycle consists of four stages: planning, action and observation, reflection, and refission. The subjects of this study are students Class X IPS 2 Semester 1 SMA Negeri 1 Bulu. Data obtained in the form of test results and non-test results. The results showed that the learning outcomes of learners increased from cycle I to cycle II that is equal to 76.00% in cycle I to 88.00% in cycle II. This classroom action researchÂ  concludes that cooperative learning with Think-Pair-Share model can improve learners' learning outcomes in geographic subjects of mapping basics material with shown to increase learning mastery of participants to achieve 88% in cycle 2. Think-Pair- Share learning model in this study proved able to increase learner activity